Analisis Tingkat Keasaman Ampas Kopi Sebagai Katalis Alternatif Sumber Energi Bio Baterai - Elmi Mahzum; Nurul Aufa; Soni Prayogi (N A T U R A L: Jurnal Ilmiah Pendidikan IPA, 2022)
In the study, we analyzed the acidity level of coffee grounds as an alternative catalyst for bio-battery energy sources, investigated how coffee grounds work as an alternative catalyst, and investigated how power is generated from variations in coffee grounds. This study used four variations of coffee grounds. Data collection was carried out by taking pH data or acidity level, voltage data, and also the length of time the LED was on from each variation of coffee grounds. The results showed that the civet arabica, original arabica, mongoose robusta, and original robusta coffee grounds respectively had pH values of 5, 5.15, 5.36, 5.6. Then the voltage is 1.35 volts, 1.27 volts, 1.11 volts, 0.994 volts. And the LED time is 417 hours, 414 hours, 409 hours, 404 hours. So that from the results obtained there is a significant relationship between the pH value and the voltage and power, that is, the smaller the pH value, the greater the voltage and power generated.